Web GIS for Airport Emergency Response - UML Model - Martina Baučić; Damir Medak (Promet (Zagreb), 2015)
The main objective of integrating Web GIS in airport emergency response should be to provide the most appropriate geospatial information to all participants. Airport emergency response still needs a model that will explain its complexity: its participants, their tasks and information needs. This paper presents the UML model of airport emergency response. Such a model facilitates a common understanding of the system by participants coming from airport, police, fire brigade, etc. It also enables institutional agreements for sharing data. The developers have got specifications of geospatial data and GIS functions imposed by participants and standards. A prototype Web GIS application is developed and presented to the users for evaluation. The prototype has shown how GIS functions can improve airport emergency response. The users have shown great interest, and they have great expectations in further integration of Web GIS in airport emergency response.